Feasibility of an Australian Knee Osteotomy Registry. Issue 2 (16th February 2016) - Vertullo, Christopher
Background: Osteotomy about the knee is a currently relatively neglected area of joint preserving research. HTO indications, frequency, complications, and outcomes of HTO in Australia remain relatively ill-defined. The success & existence of the ANJRR allows the implementation of a relatively inexpensive & comprehensive HTO Registry in Australia. Aims: Establish a comprehensive "opt-out" AKS Sponsored Australian HTO Registry using ANJRR existing resources. Establish a minimum HTO dataset for international data sharing with countries such as Sweden, New Zealand and Finland. Discussion: Benefits: AKS surgeons to define patient outcomes more accurately and objectively in High Tibial Osteotomy Will allow AKS surgeons to improve patient selection criteria for HTO Creates a multinational standard data-set to investigate a joint preserving procedure & fosters international collaboration to improve surgeons' knowledge and patient outcomes in HTO Will assist in the management of what is often a difficult problem ie osteoarthritis in younger, active patients. Barriers: Cost Data Compliance Legislation & Data Security